Експериментальне дослідження стану застосування мультимедійних технологій на уроках «Я досліджую світ» - Коваль Вікторія; Koval Viktoriia; Телецька Людмила; Teletska Lyudmila; Корбач Аліна; Korbach Alina (Видавництво «Код», 2025)
Резюме. У статті представлено результати експериментального дослідження, що вивчає стан застосування мультимедійних технологій на уроках інтегрованого курсу «Я досліджую світ» у початковій школі. Актуальність проблеми зумовлена необхідністю вдосконалення освітнього процесу в умовах дистанційного навчання та воєнного часу. Метою дослідження було вивчення проблем використання мультимедіа вчителями початкових класів.

Abstract. This article presents the results of an experimental study on the use of multimedia technologies in the integrated course «I Explore the World» in primary school. The relevance of this issue stems from ongoing educational reforms, the pervasive influence of digital technologies, and the need to improve teaching in the context of distance learning and wartime conditions. The use of multimedia in lessons provides opportunities for visualization, interactivity, and the development of a holistic understanding of the world among young learners. The study aimed to examine how primary school teachers use multimedia technologies. To achieve this, the authors used a combination of theoretical and empirical methods. The article offers a detailed analysis of the concept of «multimedia technologies», defining them as modern educational and informational tools that support the creation of interactive learning materials. Such materials stimulate students’ cognitive activity, expand their worldview, and foster the development of new skills and competencies. The authors conducted an anonymous survey via Google Forms among 146 primary school teachers from four regions of Ukraine: Chernihiv oblast, Donetsk oblast, L’viv oblast, and Kyiv. Survey results revealed that most teachers actively employ multimedia technologies, with videos (89%) and presentations (87.7%) being the most widely used. In contrast, innovative tools such as virtual laboratories and augmented reality are rarely used. The study also confirmed the positive influence of multimedia technologies on student motivation (59.6%) and knowledge acquisition (68.5%). Most teachers rated their proficiency with multimedia as high or medium, though 62.3% reported a need to further develop their skills. Key challenges included limited technical support, unstable Internet and electricity supply, a lack of high-quality content, and insufficient preparation time. The conclusions highlight recommendations for enhancing teacher training, updating technical infrastructure, and integrating multimedia technologies into the educational process.
Experimental research on the use of multimedia technologies in the integrated course «I Explore the World»
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: мультимедійні технології; інтегрований курс «Я досліджую світ»; вчителі; початкова школа; дистанційне навчання; експериментальне дослідження